(untitled) (Slavic Studies, 2025)
This paper is focused on the images of women based on exaamples from zoonymic phraseology in Macedonian and Russian. It is an attempt to determine similarities or possible differences in the zoonyms that are most often used for this purpose, and based on this to determine the stereotypes of women in both cultures and possible changes in relation to the traditional and contemporary representation of women.